(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Metal-organic frameworks (MOFs) demonstrate great potential in biosensing applications, particularly in sweat sensing, due to their high specific surface area, adjustable pore sizes, and unique catalytic properties. This review presents the advancements, fabrication techniques and potential applications of flexible sweat sensors utilizing MOFs. The background and importance of MOFs in sweat sensing were introduced, underscoring their capacity to elevate the efficiency and precision of such sensors. The structural optimisation, ligand choice, and fabrication techniques of MOFs were discussed. Various synthesis methods were explored, including electrochemical, solvothermal, room-temperature, and microwave/ultrasound-assisted approaches. The applications of MOF-based sweat sensors in trace element detection, colourimetric sensing, sports monitoring, and biomedicine were highlighted. MOFs’ high sensitivity, selectivity, and stability in these contexts underscore their potential to enhance sensor performance. The review concludes by discussing the challenges faced by flexible sweat sensors based on Metal-Organic Frameworks (MOFs), such as the diversification of detectable substances. It outlines future directions, particularly towards intelligence and high efficiency. It emphasizes the necessity of achieving high precision and multifunctionality. This review comprehensively analyses the current status and future prospects of flexible sweat sensors utilising MOFs, highlighting their significant role in advancing sweat-sensing technology.